2019
DOI: 10.1111/ijcs.12507
|View full text |Cite
|
Sign up to set email alerts
|

Are religious consumers more ethical and less Machiavellian? A segmentation study of Millennials

Abstract: Millennial consumers are increasingly becoming important actors in business that account for sufficient purchasing power. However, Millennials are infamously narcissistic and their views of ethics are more relaxed than previous generations (i.e., Baby Boomers, Generation X). Millennials remain poorly understood in general, especially in the context of developing countries. Hence, the purpose of this study was to profile this generation by segmenting Millennials in Indonesia and investigating differences betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 134 publications
(230 reference statements)
2
32
0
1
Order By: Relevance
“…In addition, intrinsic religiosity positively influenced consumer affective attitudes towards luxury brands, and that extrinsic religiosity positively influenced consumers’ self‐presentation attitudes (Arli et al, ). In other words, religious consumers with significant affective attitudes towards luxury goods are more likely to purchase luxury brands (Arli, Tkaczynski, & Anandya, ). As another example, a recent study by Dekhil et al () found that religiosity does not hinder the consumption of luxury brands.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, intrinsic religiosity positively influenced consumer affective attitudes towards luxury brands, and that extrinsic religiosity positively influenced consumers’ self‐presentation attitudes (Arli et al, ). In other words, religious consumers with significant affective attitudes towards luxury goods are more likely to purchase luxury brands (Arli, Tkaczynski, & Anandya, ). As another example, a recent study by Dekhil et al () found that religiosity does not hinder the consumption of luxury brands.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies had shown religious people will strongly align their behavior with their religious beliefs (Keller, Smith, & Smith, 2007), more likely to be against unethical acts (Razzaque & Tan, 2002;Wagner & Sanders, 2001), and having more ethical awareness (Singhapakdi, Salyachivin, Virakul, & Veerayangkur, 2000). While millennials are typically viewed to be more flexible when it comes to ethics and behavior, the influence of religion is still significant among them (Arli, Tkaczynski, & Anandya, 2019).…”
Section: Factors Affecting Ethical Behaviormentioning
confidence: 99%
“…most significant consumer (Jain, 2019a) with substantial purchasing power (Arli et al, 2019;Moreno et al, 2017) who believe that environmental sustainability is everyone's responsibility (Hanson-Rasmussen & Lauver, 2018). In response to millennials' attitudes towards environmental concerns and sustainable development, Prada (following luxury brands such as Gucci, Chanel and Burberry) and the department store Macy's have announced that they will stop using or selling animal fur starting in 2020 (Prisco, 2019).…”
mentioning
confidence: 99%